Analisis Digitalisasi Sistem Informasi Manajemen Kepegawaian (Kearsipan) Dalam Penigkatkan Kinerja Karyawan Di PT Swabina Gatra - Dhobit Nur Wildan, Mohammad; Cahyadi, Nur (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2023)
As a company in the 4.0 era, PT. Swabina Gatra certainly needs to digitize archives to improve services in safeguarding, caring for and managing company documents well. One of the applications carried out is by using Microsoft Excel. The purpose of this research is to determine the application of Microsoft Excel and how its use influences employee performance improvement at PT. Swabina Gatra in unit X. This research is qualitative research using observation, interview and documentation techniques. The results of the analysis prove that Microsoft Excel speeds up the unit work process and improves the performance of employees in unit easier search process. Furthermore, the results provided by employees obtained significant changes in performance assessments and the archives management information system, especially personnel, had an effect on employee performance.